Analysis of Media Needs Based on Visual Ethnography in Social Studies Learning in Junior High School - Makhsunah, Makhsunah; Jaenudin, Riswan; Raharjo, Makmum (Journal of Innovation and Research in Primary Education, 2025)
This study aims to analyze the needs of teachers and students for Visual Ethnography-based learning media in social studies learning in junior high schools. The Visual Ethnography approach offers a solution by presenting social and cultural data in an authentic and contextual visual form. The research method employed is a quantitative descriptive approach, supplemented by qualitative data. The research subjects consisted of 17 teachers and 211 junior high school students from nine schools in Sungai Lilin, Bayung Lencir, and Tungkal Jaya Districts, Musi Banyuasin Regency, South Sumatra Province. Data was collected through a needs questionnaire distributed using Google Forms, as well as interviews to obtain a more comprehensive picture of media needs. The results showed that students' needs for interactive, contextual, and visually based learning media related to local culture were in the high to very high category, with an average percentage of 86–93%. In contrast, the need for teachers in this aspect was in the range of 78–88%. The expected media include infographics, ethnographic videos, and visual narratives that are easy to understand and relevant to the student's learning experience. These findings confirm that Visual Ethnography-based media can increase learning engagement, understanding of social concepts, and appreciation of cultural diversity. The implications of this study highlight the need to develop innovative learning media based on Visual Ethnography to enhance social studies learning that is more meaningful, contextual, and aligned with the characteristics of junior high school students.